Implementation of serpentine locomotion. (27th April 2012) - Maity, Atanu; Majumder, Somjyoti
Cyclic changes in the body shape (body undulation) allow a serpent to locomote. These body undulations are most often 3D in nature and can be considered as combinations of two body waves on two orthogonal planes passing through a snake's body. This may be termed as Serpentine Shape Function (SSF). In case of an articulated serpentine robot these body waves are functions of joint orientations. This paper presents a detailed study on limbless locomotion and proposes a new concept of Coupled Orthogonal Joint Orientation Function (COJOF) and its implementation on an articulated serpentine robot. These gaits are not only inspired by snake locomotion but also can be extended to mimic other interesting gaits such as that of a caterpillar, inchworm and some synthetic gaits. These issues have been critically examined through experimental serpentine robot specially designed and extensively used for validation.